King, enemy, husband - Ashenden, Jackie (Harlequin presents, 2025)
"After decades under Accorsi rule, King Tiberius has fought to reclaim his crown. Yet the violent coup has left his kingdom divided. To unite his people and quell any discontent, Tiberius is left no choice...but to immediately wed his enemy's daughter, Guinevere Accorsi! Wearing Tiberius's ring frees Guinevere from her tyrannical family. Living life in the shadows is all Guinevere has known, so stepping into the spotlight as Tiberius's queen is daunting. However, her biggest challenge will be ruling over her traitorous desire for her ruthless husband..."--